Coronatine Facilitates Pseudomonas syringae Infection of Arabidopsis Leaves at Night - Panchal, Shweta; Roy, Debanjana; Chitrakar, Reejana; Price, Lenore; Breitbach, Zachary S.; Armstrong, Daniel W.; Melotto, Maeli (Frontiers in Plant Science, 2016)
In many land plants, the stomatal pore opens during the day and closes during the night. Thus, periods of darkness could be effective in decreasing pathogen penetration into leaves through stomata, the primary sites for infection by many pathogens. Pseudomonas syringae pv. tomato (Pst) DC3000 produces coronatine and opens stomata, raising an intriguing question as to whether this is a virulence strategy to facilitate bacterial infection at night. In fact, we found that (a) biological concentration of coronatine is effective in opening dark-closed stomata of Arabidopsis thaliana leaves, (b) the coronatine defective mutant Pst DC3118 is less effective in infecting Arabidopsis in the dark than under light and this difference in infection is reduced with the wild type bacterium Pst DC3000, and (c) cma, a coronatine biosynthesis gene, is induced only when the bacterium is in contact with the leaf surface independent of the light conditions. These findings suggest that Pst DC3000 activates virulence factors at the pre-invasive phase of its life cycle to infect plants even when environmental conditions (such as darkness) favor stomatal immunity. This functional attribute of coronatine may provide epidemiological advantages for coronatine-producing bacteria on the leaf surface.